2018 updated European League Against Rheumatism evidence-based recommendations for the diagnosis of gout. Issue 1 (5th June 2019) - Richette, Pascal; Doherty, Michael; Pascual, Eliseo; Barskova, Victoria; Becce, Fabio; Castaneda, Johann; Coyfish, Malcolm; Guillo, Sylvie; Jansen, Tim; Janssens, Hein; Lioté, Frédéric; Mallen, Christian D; et al.
Abstract : Although gout is the most common inflammatory arthritis, it is still frequently misdiagnosed. New data on imaging and clinical diagnosis have become available since the first EULAR recommendations for the diagnosis of gout in 2006. This prompted a systematic review and update of the 2006 recommendations. A systematic review of the literature concerning all aspects of gout diagnosis was performed. Recommendations were formulated using a Delphi consensus approach. Eight key recommendations were generated. A search for crystals in synovial fluid or tophus aspirates is recommended in every person with suspected gout, because demonstration of monosodium urate (MSU) crystals allows a definite diagnosis of gout. There was consensus that a number of suggestive clinical features support a clinical diagnosis of gout. These are monoarticular involvement of a foot or ankle joint (especially the first metatarsophalangeal joint); previous episodes of similar acute arthritis; rapid onset of severe pain and swelling; erythema; male gender and associated cardiovascular diseases and hyperuricaemia. When crystal identification is not possible, it is recommended that any atypical presentation should be investigated by imaging, in particular with ultrasound to seek features suggestive of MSU crystal deposition (double contour sign and tophi). There was consensus that a diagnosis of gout should not be based on the presence of hyperuricaemia alone. There was also a strong recommendation that all people with gout should be systematically assessed for presence of associated comorbidities and risk factors for cardiovascular disease, as well as for risk factors for chronic hyperuricaemia. Eight updated, evidence-based, expert consensus recommendations for the diagnosis of gout are proposed.